CHEMICAL COMPONENTS OF SWEET CLOVER- MELILOTUS OFFICINALIS (L.) PALL (Scientific journal of the Fergana State University, 2023)
The article is devoted to the study of the chemical components of the aboveground part of the medicinal plant Melilotus officinalis (L.) Pall (sweet clover) of the Fabaceae family. From various fractions of 75% ethanol extract of plant raw materials p-hydroxybenzoic acid, p-hydroxycoric acid, androsin, daucosterol, kaempferol 3-O-β-D-galactopyranoside and quercetin 7-O-α-L-rhamnopyranoside were isolated and identified based on the study of spectral data and chemical transformations.